2018
DOI: 10.1161/hyp.72.suppl_1.p213
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P213: Angiotensin Converting Enzyme Inhibitors (ACEi) Increase Antifibrotic Biomarkers in African American Patients With Hypertension and Left Ventricular Hypertrophy

Abstract: ACEi are first line treatment in hypertension; however, there is controversy regarding the benefit over other antihypertensive drugs. ACEi have pressure independent effects that may make them preferable for certain patients. We aimed to evaluate the impact of ACEi on antifibrotic biomarkers in hypertensive patients with left ventricular hypertrophy (LVH). We conducted a post hoc analysis of a randomized controlled trial where hypertensive African American patients with LVH and vitamin D (VTD) deficiency were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The findings by Romero et. al 5 are consistent with the results from numerous prior studies. It is true that the studied population is once again small, and the concept is not novel.…”
Section: Figuresupporting
confidence: 91%
See 1 more Smart Citation
“…The findings by Romero et. al 5 are consistent with the results from numerous prior studies. It is true that the studied population is once again small, and the concept is not novel.…”
Section: Figuresupporting
confidence: 91%
“…In the study published in this issue of the Journal of Clinical Hypertension by Romero et al, 5 the levels of pro‐ and anti‐fibrotic markers in hypertensive African American patients with LVH after one year of intensive treatment with ACE inhibitors vs. other antihypertensive medications are compared. The investigators performed a post hoc analysis of a randomized controlled trial in which hypertensive African American patients with LVH and vitamin D deficiency have been randomized to receive intensive antihypertensive therapy plus vitamin D supplementation or placebo.…”
Section: Figurementioning
confidence: 99%
“…Angiotensin‐converting enzyme inhibitor (ACEI) decreases the production of angiotensin II, subsequently decreasing the production of IL1, TNF, MMP, TGF, and vascular endothelial growth factor (VEGF). Several studies revealed that ACEI significantly reduces fibrosis formation in some organs, including the liver, heart, and kidneys [3, 28, 31, 33, 38]. Studies suggest that this drug family may affect the renin angiotensin system by inhibiting angiotensin II, stimulating prostaglandin and bradykinin, and showing antioxidant effect through the free radical scavenger action [5].…”
Section: Introductionmentioning
confidence: 99%